If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xi + -6x + 5 = 0 Reorder the terms: 5 + ix + -6x = 0 Solving 5 + ix + -6x = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + ix + -5 + -6x = 0 + -5 Reorder the terms: 5 + -5 + ix + -6x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + ix + -6x = 0 + -5 ix + -6x = 0 + -5 Combine like terms: 0 + -5 = -5 ix + -6x = -5 Add '6x' to each side of the equation. ix + -6x + 6x = -5 + 6x Combine like terms: -6x + 6x = 0 ix + 0 = -5 + 6x ix = -5 + 6x Divide each side by 'x'. i = -5x-1 + 6 Simplifying i = -5x-1 + 6 Reorder the terms: i = 6 + -5x-1
| (6*5)+(22-1y)+1y=52 | | 15+(0.75x)=y | | (2x-y)=z | | 25i^2-4=0 | | xi+14x+45=0 | | 2x+8x=6 | | 90-20x=80 | | (12+6)+1x=3x-12 | | (x^2y^2/x^4y^4)/(xy/x^2y^3) | | xi-6x+5=5 | | 5X^2-Y=10 | | (4u-2)(9-u)=0 | | X^2-1/6x | | -7x+20=3x+100 | | 12+1x+6=3x-12 | | 30=c/28 | | -21p=714 | | t+127=993 | | 24-4-8k= | | 22t=462 | | 96=-4n | | 84=3c | | g-14=46 | | m+31=-33 | | p/-4=10 | | 2x^2-12x=864 | | p-1=14 | | 91=s+26 | | 3=h/4 | | h/2=-3 | | -1=t/2 | | 6(y-4)+2y=72-8y |